Cronología absoluta para el análisis diacrónico de la secuencia de ocupación del sitio arqueológico Pashimbi, Alta Amazonía ecuatoriana An Absolute Chronology for the Diachronic Analysis of the Occupational Sequence of the Pashimbi Archaeological Site, Ecuadorian Upper Amazon - Solórzano Venegas, María Soledad (2021)
The objective of this paper is to describe the main characteristics of the occupational sequence of the Pashimbi archaeological site, one of the most complete documented sites in the Ecuadorian Upper Amazon. Radiocarbon dates, geochemical analyses, and cultural material correlation by strata allowed for a comprehensive reading of the data, determining seven times of human activity in four millennia: Colonial (183 BP), Tena (602–309 BP), Cosanga II (860 BP), Moravia (1380–1222 BP), Cosanga I (1464–1380 BP), Pambay (3110–1888 BP), and Pashimbi (4025–3450 BP). Finally, a first approximation to the subsistence forms of the groups that inhabited this territory was made.